Development of PISA-type questions on change and relationship content from level 1- 6 - Kadek Restu Astuti; Khaerani Dwi Saputri; Rendi Kurniawan; Ratu Ilma Indra Putri; Elsa Susanti; Ruth Helen Simarmata (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2025)
This study aims to develop PISA model math questions on Change and Relationship content that are valid, practical, and potentially effective to improve students' reasoning and mathematical literacy skills. The method used is design research type development studies, which consists of preliminary and formative evaluation stages. The instrument was developed through a series of evaluation stages, namely self-evaluation, expert review, one-to-one, and small group. The research subjects were VIII grade students of SMP Negeri 1 Indralaya. The questions developed included six items with difficulty levels from level 1 to level 6 and varied contexts (personal, general, and scientific). Based on the analysis of student answers, it is obtained that the questions developed by researchers can be said to be valid and practical, this is supported by the results of the validity, reliability, difficulty level, differentiating power tests quantitatively and declared practical based on the results of the analysis of student answers which show students have been able to understand the questions, the sentences used do not have double meanings and do not cause errors caused by the questions. Thus, the questions developed are declared feasible to be used to measure and train mathematical literacy and reasoning of junior high school students.